ASPEK FUNGSIONAL UPACARA MABAYUH OTON - Ida Ayu Komang Arniati (Pascasarjana Universitas Hindu Indonesia, 2017)
Mabayuh Oton ceremony has several special functions that are first functioning religiously. This ceremony is one of the manusa yadnya ceremonies held in Bali which aims to free human beings from the shackles of Sad Ripu or the nature of the gamut brought from birth. After mabayuh oton has been executed, the bad traits will be controlled and emerging traits that are in accordance with the norms of moral Hindu religion and the basis of a holy life. Secondly, itserves as a form of local culture of the Balinese community which until now is still held. Third, This ceremony serves to the character building of children. According to the naturalistic view of the children character beside of being formed by the environmental factors, their character are also built innate factors.